2012
DOI: 10.1126/science.1225468
|View full text |Cite
|
Sign up to set email alerts
|

A Fully Size-Resolved Perspective on the Crystallization of Water Clusters

Abstract: The number of water molecules needed to form the smallest ice crystals has proven challenging to pinpoint experimentally. This information would help to better understand the hydrogen-bonding interactions that account for the macroscopic properties of water. Here, we report infrared (IR) spectra of precisely size-selected (H(2)O)(n) clusters, with n ranging from 85 to 475; sodium doping and associated IR excitation-modulated photoionization spectroscopy allowed the study of this previously intractable size dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
257
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(281 citation statements)
references
References 41 publications
22
257
0
2
Order By: Relevance
“…For narrower pores, subcritical ice clusters may be produced at a high rate, but cannot grow to the critical size due to the confinement. This view is supported by experimental Pradzynski et al, 2012) and modeling studies (Moore et al, 2012;Li et al, 2011;Reinhardt and Doye, 2012), which estimate that critical ice clusters consist of 70 to 275 molecules in the temperature range from 195 to 231 K corresponding to r c = 1.2-1.8 nm if one assumes a spherical shape of the critical clusters. Also for larger pores and at higher temperatures, the radius of a critical cluster with spherical shape seems to determine the melting and freezing temperatures in pores.…”
Section: Marcolli: Deposition Nucleation 2075supporting
confidence: 56%
“…For narrower pores, subcritical ice clusters may be produced at a high rate, but cannot grow to the critical size due to the confinement. This view is supported by experimental Pradzynski et al, 2012) and modeling studies (Moore et al, 2012;Li et al, 2011;Reinhardt and Doye, 2012), which estimate that critical ice clusters consist of 70 to 275 molecules in the temperature range from 195 to 231 K corresponding to r c = 1.2-1.8 nm if one assumes a spherical shape of the critical clusters. Also for larger pores and at higher temperatures, the radius of a critical cluster with spherical shape seems to determine the melting and freezing temperatures in pores.…”
Section: Marcolli: Deposition Nucleation 2075supporting
confidence: 56%
“…Electron diffraction experiments performed in the 1980's suggested that water clusters become crystalline in the size range 200-1000 molecules [12]. This result was confirmed by vibrational IR spectroscopy experiments on pure water and Na-doped clusters [10,13], which suggest an onset of crystallization at about 275 water molecules [13]. Computer simulations support the assumption of amorphous-tocrystalline transition occurring above 200 molecules [14].…”
Section: Introductionmentioning
confidence: 59%
“…The cluster sizes we probe here (see below) are smaller than the onset of crystallization in water clusters. 10 We therefore assume that solid state band structure effects, e.g., band dispersion, do not play a role in our sample. It seems nevertheless plausible that aggregation will have some influence on the β parameter.…”
Section: Introductionmentioning
confidence: 99%